2020
DOI: 10.1101/2020.06.05.135905
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anesthetics fragment hippocampal network activity, alter spine dynamics and affect memory consolidation

Abstract: 20General anesthesia is characterized by reversible loss of consciousness accompanied by 21 transient amnesia. Yet, long-term memory impairment is an undesirable side-effect. How 22 different types of general anesthetics (GAs) affect the hippocampus, a brain region central to 23 memory formation and consolidation, is poorly understood. Using extracellular recordings, 24 chronic 2-photon imaging and behavioral analysis, we monitor the effects of isoflurane (Iso), 25 medetomidine/midazolam/fentanyl (MMF), and ke… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 115 publications
(182 reference statements)
1
8
0
Order By: Relevance
“…The distribution of mean ΔF/F values was significantly shifted to higher values during wakefulness compared to anesthesia (Fig. 3B; 23 ± 24% vs. 11 ± 10%, mean ± s.d., p<0.001, two-sided Wilcoxon rank sum test), in qualitative agreement with recent findings in CA1 (Yang et al, 2020). The distribution of mean ΔF/F values for the awake condition showed a pronounced tail of large events, with a substantial fraction reaching >100% mean F/F.…”
Section: Large and Prolonged Calcium Transients During Wakefulness And Locomotionsupporting
confidence: 91%
“…The distribution of mean ΔF/F values was significantly shifted to higher values during wakefulness compared to anesthesia (Fig. 3B; 23 ± 24% vs. 11 ± 10%, mean ± s.d., p<0.001, two-sided Wilcoxon rank sum test), in qualitative agreement with recent findings in CA1 (Yang et al, 2020). The distribution of mean ΔF/F values for the awake condition showed a pronounced tail of large events, with a substantial fraction reaching >100% mean F/F.…”
Section: Large and Prolonged Calcium Transients During Wakefulness And Locomotionsupporting
confidence: 91%
“…The STTC, a metric that tracks correlations between spike trains and is robust to changes in firing rate, was calculated as previously described 51,93 (Figure 3A): where P A is defined as the proportion of spikes in spike train A that falls within ±Δt of a spike from spike train B. T A is defined as the proportion of time that occurs within (is “tiled” by) ±Δt from the spikes of spike train A. The same applies for P B and T B .…”
Section: Methodsmentioning
confidence: 99%
“…Imaging dendritic spines in awake animals is important because acute exposure to various anesthetics has been documented to increase spine formation in both cortical and hippocampal neurons in young rats ( 39 , 40 ) and decrease the elimination of filopodia-type dendritic protrusions in vivo in 1-mo-old mice ( 57 ). More importantly, a recent study has systematically investigated the effects of anesthesia on dendritic spine dynamics of CA1 pyramidal neurons after repeated exposure ( 41 ), as it is necessary for chronic imaging studies. Isoflurane, the anesthetic used in most in vivo imaging studies, was shown to increase spine turnover and spine density over five imaging sessions with 4-d intervals ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, a recent study has systematically investigated the effects of anesthesia on dendritic spine dynamics of CA1 pyramidal neurons after repeated exposure ( 41 ), as it is necessary for chronic imaging studies. Isoflurane, the anesthetic used in most in vivo imaging studies, was shown to increase spine turnover and spine density over five imaging sessions with 4-d intervals ( 41 ). Thus, in order to observe spine dynamics under physiological conditions, imaging in awake mice, as in the present study, is essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation